Nanoelipsoides de Fe y FeCo con Microestructuras Diseñadas Bioinspiradas en la Bacteria Magnetotáctica - Luna Criado, Carlos; Mendoza Reséndez, Raquel (Universidad Autónoma de Nuevo León, 2013)
ABSTRACT In the present contribution, we propose and analyze some synthetic strategies for the preparation of uniform magnetic nanoellipsoids with tailored microstructures that exhibit similarities to the arrangement of the magnetosomes (small magnetic nanocrystals) biomineralized by magnetotactic bacteria. Given their hard magnetic properties at room temperature, the resulting nanoellipsoids can be used as permanent nanomagnets in a large variety of technological fields, including information recording media, magnetic bioseparators and biosensors, localized hyperthermia therapies and drug delivery.